Legitimasi Penerbitan Sertifikat Hak Atas Tanah di Wilayah Perairan Laut dalam Hukum Agraria Indonesia - Naufal Rodiyatul Maula; Yuniar Rahmatiar; Muhammad Abas; Suyono Sanjaya (Universitas Semarang, 2025)
This research examines the legality of issuing ownership certificates (SHM) and building use rights (HGB) in marine areas, a practice that continues to appear in land administration despite the absence of a clear legal foundation. The fundamental problem is seen in the inconsistency between the Basic Agrarian Law, the legal regime governing marine spatial areas, and administrative practices that treat the sea as if it were eligible to become an object of land rights. Using a normative juridical technique with statutory and conceptual approaches, complemented by an examination of relevant administrative practices, this study assesses the compatibility of such certifications with the principle of legal certainty. The findings indicate that marine waters do not meet the criteria required to constitute a purpose of land rights, making the issuing of SHM/HGB in these locations legally defective and susceptible to cancellation through internal administrative correction or judicial review before the administrative court. Another finding highlights the legal uncertainty faced by certificate holders and third parties due to the inherently non-privatizable nature of marine areas. The originality of this research resides in its comprehensive investigation of the discord between agrarian and maritime legal regimes and its proposed regulatory reforms to prevent the recurrence of land-rights certification in marine spaces. Penelitian ini mengkaji legalitas penerbitan Meskipun tidak memiliki landasan hukum yang jelas, sertifikat hak milik (SHM) dan hak guna bangunan di perairan laut masih banyak digunakan dalam prosedur administrasi pertanahan. Permasalahan utamanya terlihat pada ketidaksinkronan antara Undang-Undang Pokok Agraria, rezim hukum ruang laut, serta kewenangan administrasi pertanahan yang memperlakukan laut seolah-olah dapat menjadi objek hak atas tanah. Penelitian ini menggunakan teknik yuridis normatif dengan pendekatan perundang-undangan dan konseptual, serta mengevaluasi prosedur administratif penting untuk menilai kepatuhannya terhadap asas kepastian hukum. Hasil penelitian menunjukkan bahwa laut tidak memenuhi kualifikasi sebagai objek hak atas tanah sehingga penerbitan SHM/HGB di wilayah tersebut merupakan tindakan administratif yang tidak sah dan berpotensi dibatalkan melalui mekanisme koreksi internal maupun peradilan tata usaha negara. Temuan lainnya adalah adanya risiko ketidakpastian hukum bagi pemegang sertifikat dan pihak ketiga akibat status objek yang tidak dapat dilekati hak privat. Orisinalitas penelitian ini terletak pada investigasi lengkap tentang ketidaksesuaian antara undang-undang pertanian dan kelautan serta rekomendasi penataan regulasi yang dapat mencegah berulangnya penerbitan hak atas tanah di wilayah laut.